Modeling the pressure drop behavior of cleanable dust filters during pressure-controlled operation. Issue 18 (12th December 2017) - Laminger, T.; Stecher, M.; Mauschitz, G.; Höflinger, W.
ABSTRACT: Cleanable dust filter media are typically used in huge baghouse filter apparatuses. Thereby, the regeneration by back-pulsing from the clean gas side is done by either time-controlled or pressure-controlled operation, whereas the latter is more common. Hence, the need for a detailed knowledge of the clogging and filtration mechanisms during long time operation of a pressure-controlled filter aging arises. A mathematical model describing the pressure drop evolution during time-controlled filter aging has been developed. The core of the developed model is the concept of dust masses that distribute themselves on a specific particle deposition area inside and on the surface of the filter medium. By altering this particle deposition area, various clogging mechanisms, occurring during an aging procedure, are covered by the model. In this work, the model was adapted and coefficient parameters adjusted for pressure-controlled filter regeneration operation. A multitude of pressure-controlled test runs were performed in a specially designed filtration apparatus. From these tests, process-specific parameters were regressed and used to model the respective pressure drop curves. These model pressure drop curves show good accordance both quantitatively and qualitatively to experimental data and give a detail view on different clogging mechanisms.